Transglutaminase 2 regulates terminal erythroid differentiation via cross-linking activity - Zhang, Yingying; Shi, Lifang; Yang, Ke; Liu, Xuehui; Lv, Xiang (Frontiers in Cell and Developmental Biology, 2023)
Transglutaminase 2 (TGM2) is a versatile enzyme that modulates cell survival and differentiation. However, its role in terminal erythroid differentiation is poorly understood. In this study, we investigated the function of TGM2 in primary fetal liver erythroid differentiation. We predicted TGM2 as an upstream regulator via ingenuity pathway analysis (IPA), and found that its expression was increased at both RNA and protein level during terminal erythroid differentiation. TGM2 cross-linking activity inhibitors GK921 and Z-DON suppressed erythroid maturation and enucleation, while its GTPase inhibitor LDN27219 had no such effect. Z-DON treatment arrested differentiation at basophilic erythroblast stage, and interfered with cell cycle progression. RT-PCR demonstrated decreased GATA-1 and KLF1, and disarranged cyclin, CDKI and E2F family genes expression after Z-DON treatment. In conclusion, TGM2 regulates terminal erythroid differentiation through its cross-linking enzyme activity.